2007
DOI: 10.1007/s11947-007-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture on Trichoderma Conidia Production on Corn and Wheat Bran by Solid State Fermentation

Abstract: In the present work, the use of low-cost substrates to produce Trichoderma spores was evaluated. Rice, corn bran, and wheat bran were used as solid substrate to grow Trichoderma harzanium sp., Trichoderma viride sp., Trichoderma koningii sp., and Trichoderma polysporum sp. No external nutrient sources were added to the solid substrate that was only moisturized with deonized water, sterilized, inoculated, and cultivated at 30°C for 7 days. Wheat bran showed to be the most suitable substrate to produce Trichoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 24 publications
2
56
0
6
Order By: Relevance
“…Spore count was adjusted to 1 9 10 7 spores/ml. Fungus was maintained in spore form supported in wheat bran at 4°C [13].…”
Section: Microorganisms and Maintenancementioning
confidence: 99%
“…Spore count was adjusted to 1 9 10 7 spores/ml. Fungus was maintained in spore form supported in wheat bran at 4°C [13].…”
Section: Microorganisms and Maintenancementioning
confidence: 99%
“…Although the results showed that the water content of the carrier did not significant differences among the carrier material formulations. [13] stated that moisture of the solid-substrate are not the only factor that affected Trichoderma conidia production, but in the solid state fermentation is also affected by the solid composition and structure, as well as by the cultivated strain.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ravinder et al [30] and Hoebler et al [31], relatively high spore production by A. niger using rice bran and barley were detected as a result of high protein concentration in the medium. Likewise, Cavalcante et al [32] reported that wheat bran was one of the preferable substrate for high spore production because it possessed better water retention, greater porosity and higher nutrients content. Wheat bran is abundant with nutrients that able to be absorbed in the fungi and also capable of retaining sufficient water for the fungi to flourish even in the SsF.…”
Section: Spore Production From Various Agricultural Residualsmentioning
confidence: 99%